The Issue of Private-Law Debts and Claims Between Bosnia and Herzegovina and Austria After the Dissolution of the Austro-Hungarian Monarchy - Užičanin, Salkan (Historical Thought, 2025)
This paper analyzes the economic problems that emerged between Austria and Bosnia and Herzegovina, or rather the Kingdom of Serbs, Croats and Slovenes, following the dissolution of the Austro-Hungarian Monarchy. The focus is placed on resolving the private-law debts and claims of citizens of the two countries. This complex issue had already been examined during the peace negotiations in Paris, but the solutions offered in the Saint-Germain Peace Treaty proved unsatisfactory, as numerous problems arose during their implementation. The two sides held repeated negotiations on international conferences and forums, as well as in bilateral meetings. However, these negotiations remained overshadowed by political and other economic issues, staying on the margins and often being conditioned by demands that were unacceptable to the other side. Under public pressure, but also due to economic necessity, the dispute over debts was ultimately resolved at the end of February 1923.